М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
ivanrumyantsev1
ivanrumyantsev1
04.03.2020 11:10 •  Математика

Адание 2.
2:2+1,8-3
(1,05-%) + 4
16 8
217


Адание 2.2:2+1,8-3(1,05-%) + 416 8217

👇
Ответ:
orlovaelvira
orlovaelvira
04.03.2020

5,4

Пошаговое объяснение:

см фото


Адание 2.2:2+1,8-3(1,05-%) + 416 8217
4,6(31 оценок)
Открыть все ответы
Ответ:
Ochoba007
Ochoba007
04.03.2020

       x dx       1       2x dx         1       d(7+x²)        1

   ∫ =  ∫ = ∫ = ln(7+x²)+C

       7+x²      2        7+x²          2        7+x²           2  

                                 

[1/2 *ln(7+x²)+C ]¹= 1/2*[ 2x /(7+x²)+0]= x /(7+x²)

          x+18                (x-2)+20             1       2(x-2)                            dx

 2) ∫dx=∫ dx=  ∫ dx+20 ∫ =

        x²-4x-12            (x-2)²-16              2    (x-2)²-16                 (x-2)²-16   

     1                                          1          |  x-2-4    |           1                             5         | x-6  |

= *ln|(x-2)²-16|+20 * *ln || +C= *ln |x²-4x-12|+*ln || +C  

      2                                     2*8           |  x-2+4  |            2                             4         | x+2 |  

          

3) ∫(3-x) cosx dx=[ u=3-x , du=-dx ,  dv=cosx dx ,  v=sinx ] =(3-x)sinx+∫ sinx dx=

  =(3-x)sinx-cosx+C

   [(3-x)sinx-cosx]¹= -sinx+(3-x)cosx+sinx +0=(3-x)cosx

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

4,6(16 оценок)
Ответ:
lizasergeeva001
lizasergeeva001
04.03.2020

       x dx       1       2x dx         1       d(7+x²)        1

   ∫ =  ∫ = ∫ = ln(7+x²)+C

       7+x²      2        7+x²          2        7+x²           2  

                                 

[1/2 *ln(7+x²)+C ]¹= 1/2*[ 2x /(7+x²)+0]= x /(7+x²)

          x+18                (x-2)+20             1       2(x-2)                            dx

 2) ∫dx=∫ dx=  ∫ dx+20 ∫ =

        x²-4x-12            (x-2)²-16              2    (x-2)²-16                 (x-2)²-16   

     1                                          1          |  x-2-4    |           1                             5         | x-6  |

= *ln|(x-2)²-16|+20 * *ln || +C= *ln |x²-4x-12|+*ln || +C  

      2                                     2*8           |  x-2+4  |            2                             4         | x+2 |  

          

3) ∫(3-x) cosx dx=[ u=3-x , du=-dx ,  dv=cosx dx ,  v=sinx ] =(3-x)sinx+∫ sinx dx=

  =(3-x)sinx-cosx+C

   [(3-x)sinx-cosx]¹= -sinx+(3-x)cosx+sinx +0=(3-x)cosx

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

4,4(53 оценок)
Это интересно:
Новые ответы от MOGZ: Математика
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ